Reflecting Elements of Listening Comprehension; Survey - Shaymanovich, Khasan Abdinazarov; Pulatovna, Zebo Aminova; Axatovna, Olima Khalilova (International Journal of Psychosocial Rehabilitation, 2020)
Listening comprehension is a complex process which requires a lot of aspects to be taken into consideration. In particular, following and understanding film in FL is even more difficult comparing to listening to just an episode in EFL (including ESP) teaching. There are no specific rules to follow during listening as in teaching pronunciation or grammar. This study explores to show students can improve their listening comprehension skills by watching films and what aspects (grammar and pronunciation rules, accents and dialects, terminology, traits and behavior of the people, situation) they need to follow in order to understand whole film and comprehend oral production of the film characters. To find out about the impact of those issues, we carried out experiments with students at the Faculty of Oil and gas, Karshi Engineering- Economic institute, Karshi, Uzbekistan. The 60 respondents - 3rd year students were involved in the questionnaire survey aimed at their motivation to watch the films and some elements which help them to better understand content of audio-visual material. Besides, we did an interview with students to identify their attitudes and opinions about the use of films in ESP classes. To accomplish our research we used the five-point Likert Scale.